Addressing anthelmintic resistance in Haemonchus contortus strains in small ruminants through alternative strategies with a focus on Moringa oleifera extracts - Du Toit, C.J.L. (University of Pretoria, 2025)
Dissertation (MSc (Agric) (Animal Science: Animal Nutrition))--University of Pretoria, 2024.